Arabic in the specialised literature on translation and interpreting - Zanón, Jesús (Estudios de Traducción, 2011)
The purpose of this work is to investigate the research activity on Arabic translation and interpretation, to explore the most widely discussed topics, and to depict their recent evolution. The most remarkable results can be summarized as follows. An interest on Arabic translation studies is confirmed: it starts in the XIX century and extends through the XX century, where there is a slight but constant increase on the number of publications up to the 1980s. From the 1990s onwards, a big bibliography outbreak, that is maintained and intensified up to the present day, takes place. Likewise, from the 1990s onwards, the rise of new research topics is attested, just as it happens in translation studies research in general, although in the case of Arabic, traditional topics keep being strongly supported.